Xây dựng các hệ tri thức y học cổ truyền Việt Nam - Phương, Nguyễn Hoàng (Journal of Computer Science and Cybernetics, 2016)
In this work we dealt with the development tendency of Medical Informatics in general and present background conceptions of a knowledge based system. Some knowledge system developed and under development in Acupuncture, Massage and Acupression, Chrono-Acupuncture, Intergrated Medicine and Vietnamese Herbal Plants are briefly described.